AJUSTE FISCAL E OFENSIVA CONTRA OS TRABALHADORES BRASILEIROS: UMA CRÍTICA MARXISTA (REVISTA DIREITOS, TRABALHO E POLÍTICA SOCIAL, 2018)
O ajuste fiscal é uma das múltiplas dimensões da ofensiva burguesa contra a classe trabalhadora. Este artigo teve como objetivo geral fornecer uma crítica marxista à atual conjuntura de ajuste fiscal no Brasil e, especificamente, pretendeu destacar a natureza burguesa deste processo. A perspectiva metodológica utilizada foi a da totalidade, com enfoque na luta entre as classes fundamentais no capitalismo. A trajetória percorrida indicou que, nos marcos da crise estrutural do capital e da redefinição do papel do Estado capitalista, o ajuste fiscal possui natureza reacionária e conservadora e deve ser entendido como um projeto político da classe burguesa contra os trabalhadores brasileiros.   FISCAL AUSTERITY AND OFFENSIVE AGAINST THE BRAZILIAN WORKERS: A MARXIST CRITIQUEAbstract: The fiscal austerity program is one of the many dimensions of the bourgeois offensive against the working class. This article had the general aim of providing a Marxist critique to the current agenda of the fiscal austerity program in Brazil, and, specifically, it intended to highlight the bourgeois nature of this process. The methodological perspective used was the totality, with a particular focus on the struggle between the fundamental classes in capitalism. The pattern followed indicated that, in the context of the structural crisis of capital and the redefinition of the role of the capitalist State, the fiscal austerity agenda is, in its nature, reactionary and conservative and needs to be understood as a political project from the bourgeois class against the Brazilian workers. Key-Words: Fiscal austerity. Social expenditure. Marxist critique.